(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The mastery of reciting the Quran with lahjah arabiah is a form of skill that every Quran reciter must have. The decline in mastery of reciting with lahjah arabiah will inhibit the entire reciting of the Quran with songs that includes the components of tajwid, fasohah, sawt and tarannum. This study will analyse the level of mastery of reciting the Quran with melody among the qari and qariah champions at the National Quran Recitation Competition (MTQA) of Malaysia. The methodology of this study is a quantitative design that collects data from questionnaires and interviews with field experts. A total of seventeen samples of reciting videos by the champions of qari and qariah at the National level of Malaysia were obtained involving a total of 17 people. Overall, the results of the study found that the level of mastery of al-Quran recitation by qari and qariah in the National Level Quran Recitation Competition in Malaysia is at a min value of 3.05 is medium high. In the tajwid and fasohah section, the min value is 3.41 which is medium high. The tarannum section, the min value of 2.89 is medium low, while the sawt section, the min value of 2.86 is at a medium low level. The implication of the study explained that the weakness of mastery of lahjah arabiah reciting needs to be improved in a more focused and planned manner so that the participants of qari and qariah can better master the recitation of lahjah arabiah.